Mastering Windows Vista business : - Minasi, Mark (Wiley Pub., 2007)
Learn to install, configure, run, and troubleshoot the professional versions of Vista in this comprehensive new guide from two leading Windows authorities. From Vista's all-new interface, 32-bit/64-bit architecture, and advanced security features to its fantastic new capabilities for audio and video recording, editing, and broadcasting, you’ll get the techniques and task-by-task instruction you need to master this dramatically different OS.